The Fire Within: Microbes Inflame Tumors - Gagliani, Nicola; Hu, Bo; Huber, Samuel; Elinav, Eran; Flavell, Richard A. (Cell, 2014)
The immune system and the microbiota mutually interact to maintain homeostasis in the intestine. However, components of the microbiota can alter this balance and promote chronic inflammation, promoting intestinal tumor development. We review recent advances in understanding the complex interactions between the microbiota and the innate and adaptive immune systems and discuss their potential to lead us in new directions for understanding cancer biology and treatment.